Ictal semiology, functional anatomy and multimodal diagnostic in patients with insular epilepsies - Stefan, Hermann; Gollwitzer, Stephanie (Acta Epileptologica, 2019)
Background: The insula is a hidden part in the cerebral cortex. Insular epilepsy is underrecognized and it bears a special risk for misdiagnosis with regard to nonepileptic seizures or wrong localization of epileptic seizures. Case presentations: The manuscript describes 2 cases with ictal semiology of paresthesia and pain followed by hyperkinetic movements, noninvasive findings of source localization and/or invasive SEEG exploration. Conclusion: Magnetic source imaging, ictal SPECT as noninvasive and invasive recordings with depth electrodes (SEEG) can provide important preoperative information for the involvement of insular and periinsular regions in focal pharmacoresistant epilepsies. The optimal use of these methods presupposes extensive knowledge of ictal semiology and other clinical characteristics. The clinical localization hypothesis can be optimally proofed by SEEG exploration.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Ictal semiology; Insular epilepsy; MEG/EEG; SEEG; Source localization